Glycogen synthase kinase‐3β activity plays a key role in the antitumor effect of nafamostat mesilate in pancreatic cancer cells. Issue 1 (31st August 2017) - Haruki, Koichiro; Shiba, Hiroaki; Shimada, Yohta; Shirai, Yoshihiro; Iwase, Ryota; Fujiwara, Yuki; Uwagawa, Tadashi; Ohashi, Toya; Yanaga, Katsuhiko
Abstract: Pancreatic cancer is often resistant to chemotherapy. We previously showed the efficacy of combination treatment using gemcitabine and nafamostat mesilate (FUT‐175) for patients with unresectable pancreatic cancer. However, the mechanisms that affect the sensitivity of FUT‐175 are not fully understood. The purpose of the present study was to clarify the mechanism of the sensitivity to FUT‐175, with a focus on the activity of glycogen synthase kinase‐3β (GSK‐3β). In vitro, we assessed sensitivity to FUT‐175 in human pancreatic cancer cell lines (PANC‐1 and MIAPaCa‐2) and difference of signaling in these cells by cell proliferation assay, Western blot analysis and microarray. Next, we assessed cell viability, apoptotic signal and nuclear factor‐kappa B (NF‐κB) activity in response to treatment with FUT‐175 alone and in combination with GSK‐3 inhibitor or protein phosphatase 2A (PP2A) by cell proliferation assay, Western blot analysis and enzyme‐linked immunosorbent assay. Phosphorylated GSK‐3β level was significantly higher in MIAPaCa‐2 (high sensitivity cell) than in PANC‐1 (low sensitivity cell). Cell viability and NF‐κB activity were significantly decreased by addition of GSK‐3 inhibitor to FUT‐175, and levels of cleaved caspase‐8 were increased by inhibition of GSK‐3. PP2A inhibitor increased the levels of phosphorylated GSK‐3β and sensitized both cell lines to FUT‐175 as measured by cell viability and apoptotic signal. The results indicate that GSK‐3β activity plays a key role in the antitumor effect of FUT‐175 in pancreatic cancer cells, and regulation of GSK‐3β by PP2A inhibition could be a novel therapeutic approach for pancreatic cancer. Abstract : PP2A inhibitor increased the levels of phosphorylated GSK‐3β and sensitized both cell lines to FUT‐175 as measured by cell viability and apoptotic signal.